2014
DOI: 10.3390/v6104005
|View full text |Cite
|
Sign up to set email alerts
|

KSHV miRNAs Decrease Expression of Lytic Genes in Latently Infected PEL and Endothelial Cells by Targeting Host Transcription Factors

Abstract: Kaposi’s sarcoma-associated herpesvirus (KSHV) microRNAs are encoded in the latency-associated region. Knockdown of KSHV miR-K12-3 and miR-K12-11 increased expression of lytic genes in BC-3 cells, and increased virus production from latently infected BCBL-1 cells. Furthermore, iSLK cells infected with miR-K12-3 and miR-K12-11 deletion mutant viruses displayed increased spontaneous reactivation and were more sensitive to inducers of reactivation than cells infected with wild type KSHV. Predicted binding sites f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 65 publications
4
35
0
Order By: Relevance
“…MiR-K3 has been reported to maintain viral latency by targeting nuclear factor I/B, MYB, C/EBPα and Ets-1 [19, 39]. In addition, we have found that miR-K3 directly targets GRK2/CXCR2/AKT pathway to promote migration and invasion of endothelial cells [40].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…MiR-K3 has been reported to maintain viral latency by targeting nuclear factor I/B, MYB, C/EBPα and Ets-1 [19, 39]. In addition, we have found that miR-K3 directly targets GRK2/CXCR2/AKT pathway to promote migration and invasion of endothelial cells [40].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, miR-K3 contributes to the maintenance of latency by decreasing RTA expression via down-regulation of MYB, C/EBPα and Ets-1 [39]. We have recently revealed that miR-K3 directly targets G protein-coupled receptor kinase 2 (GRK2) to promote endothelial cell migration and invasion by activating CXCR2/AKT signaling [40].…”
Section: Introductionmentioning
confidence: 99%
“…During differentiation of CD34+ progenitor cells to a myeloid lineage that supports productive infection, the levels of these miRNAs drop indicating that both viral and host miRNAs regulate viral latency and reactivation. Viral miRNAs also regulate cellular pathways to help maintain viral latency, as demonstrated for KSHV, where viral miRNAs mediate the repression of the Replication and Transcription Activator (RTA) [55,56] and target the NF-kB pathway [57,58]. By both direct and indirect repression of key viral transactivators, viral and cellular miRNAs thus inhibit lytic replication and aid both the establishment and maintenance of viral latency.…”
Section: Micrornas In Latency and Reactivationmentioning
confidence: 96%
“…Viral miRNAs have also been shown to be important for gammaherpesvirus reactivation from latency, typically by playing inhibitory roles. This is mediated either by direct repression of Rta or Zta, viral transcription factors that initiate lytic cycle replication, or indirectly through repression of the pathways leading to transcription of these factors (60)(61)(62)(63)(64). The KSHV homolog of miR-155, miR-K12-11, specifically was shown to inhibit Rta by inhibiting transcription factors known to activate the Rta promoter (64).…”
Section: Discussionmentioning
confidence: 99%